EFFICACY OF IMMUNOMODULATORS FOR TREATMENT OF ENDOMETRITIS IN COWS - SARMA, O K; SINGH, BALRAJ; SINGH, M P; TIWARY, B K; SINHA, M P (The Indian Journal of Animal Reproduction, 2023)
The relative efficacy of intrauterine (IU) immunomodulators, viz., E. coll lipopolysaccharide (LPS), OysterGlycogen (OG) and Autologus Plasma (AP) in the treatment of endometritis in cows was investigated. Fortyendometritic cows were randomly divided into 4 groups (n=10) and were marked as T1 T2, T3 and T 4. The T 4 groupwas kept as control with single dose Phosphate Buffer Solution(PBS) infusion. White side test, pH and bacterialload were estimated before and after treatment in uterine discharge for diagnosis and clinical evaluation, respectivelywhile at estrus. At post treatment subsequent estrus A.I. was done in the recovered cows. Recovery and conceptionpercentage out of total animals treated were 100.00, 80.00, 60.00, 20.00% and 90.00, 80.00, 50.00 and 20.00 ingroup T1 T2, T3 and T4, respectively. The results indicated the efficacy and possibility of using E.coli LPS, OGand AP as alternative therapy of endometritis in crossbred cows.
Keywords: Endometritis; Cows; Treatment; lmmunomodulators